The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1590/1806-9282.20220960
|View full text |Cite
|
Sign up to set email alerts
|

The clinical value of lung ultrasound in premature infants with bronchopulmonary dysplasia

Abstract: OBJECTIVE: This study aimed to explore the risk factors of bronchopulmonary dysplasia in premature infants and the clinical application value of lung ultrasound in the diagnosis of bronchopulmonary dysplasia. METHODS: A total of 80 premature infants with a gestational age of <32 weeks or a birth weight of <1,500 g who were treated in our hospital from January to August 2021 were randomly divided into a bronchopulmonary dysplasia group (n=12) and a non-bronchopulmonary dysplasia group (n=62). The clinical data,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One of the presented studies was a meta-analysis [31], which showed the early LUS with a less extensive score has 70-80% sensitivity and 80-87% specificity in predicting BPD. Other studies, including prospective ones [32,33], confirmed this finding, even if a relatively low number of extremely preterm infants were enrolled; moreover, in these studies, LUS was more accurate than CXR for BPD prediction. Other studies confirmed the utility of LUS performed at 14 days of life in extremely preterm infants [35] and the role of lung consolidations detected in the first weeks of life for the prediction of BPD [36].…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…One of the presented studies was a meta-analysis [31], which showed the early LUS with a less extensive score has 70-80% sensitivity and 80-87% specificity in predicting BPD. Other studies, including prospective ones [32,33], confirmed this finding, even if a relatively low number of extremely preterm infants were enrolled; moreover, in these studies, LUS was more accurate than CXR for BPD prediction. Other studies confirmed the utility of LUS performed at 14 days of life in extremely preterm infants [35] and the role of lung consolidations detected in the first weeks of life for the prediction of BPD [36].…”
Section: Discussionmentioning
confidence: 55%
“…Xu et al [ 32 ] compared the predictive role of LUS and CXR in preterm infants. They conducted a study with 248 eligible infants, of which 80 were randomly enrolled and divided into a BPD group ( n = 12) and a non-BPD group ( n = 62); they showed that the diagnostic accuracy of lung ultrasound for bronchopulmonary dysplasia was better than that of X-rays (98.7% vs. 85.1%).…”
Section: Resultsmentioning
confidence: 99%